Implementasi Gamifikasi Untuk Meningkatkan Keterampilan Bahasa Sunda Melalui Aplikasi Android dengan Extreme Programming - Prajoko; Al-Fachri, M Herdi; Asep Budiman Kusdinar (Journal of Informatics Management and Information Technology, 2025)
Sundanese is one of the local languages taught at the elementary school level in West Java. Unfortunately, students’ enthusiasm and ability especially in understanding undak-usuk basa or speech level variations in Sundanese remain relatively low. This issue is generally caused by the lack of interactive teaching approaches and the absence of digital media that allow students to learn independently outside school hours. This condition poses a threat to the preservation of local languages among the younger generation. To address this problem, this study developed an Android-based Sundanese learning application using a gamification approach and the Extreme Programming (XP) method, with the goal of increasing students’ interest and understanding of undak-usuk basa independently. The development process involved five main stages: Planning, Design, Coding, Testing, and Release. Key features of the application include interactive quizzes, a coin-based point system, level progression, rewards, traditional Sundanese music, and a user interface designed to suit children. The application was developed using Android Studio with Kotlin and utilized Firebase Realtime Database for storage. To evaluate its effectiveness, pre-tests and post-tests were conducted on third-grade elementary students. The results showed an increase in the average score from 34 to 88 after using the application. These findings indicate that implementing gamification in an educational app based on the XP method can significantly enhance students’ interest and competence in learning the Sundanese language.